Analisis Akuntansi Untuk Transaksi Mata Uang Asing Pada Pt. Appipa Indonesia - Annisa Urrohmah; Susi Ratna Sari; Shelvina Dwie Oktavia (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This article will analyze foreign currency transactions at PT. Appipa Indonesia. In import-export transactions related to two different countries, using different currencies, namely foreign currency and local currency. Foreign currency transactions in their treatment can affect the financial statements of sales, purchases, accounts payable, receivables, and so on. This research method is descriptive qualitative. PT. Appipa Indonesia has implemented accounting treatment in accordance with PSAK No.10 regarding exchange differences on foreign currency transactions.